2018
DOI: 10.1080/14693062.2018.1534723
|View full text |Cite
|
Sign up to set email alerts
|

Power interplay between actors: using material and ideational resources to shape local adaptation plans of action (LAPAs) in Nepal

Abstract: Deliberation over how to adapt to short or long-term impacts of climate change takes place in a complex political setting, where actors' interests and priorities shape the temporal dimension of adaptation plans, policies and actions. As actors interact to pursue their individual or collective interests, these struggles turn into dynamic power interplay. In this article, we aim to show how power interplay shapes local adaptation plans of action (LAPAs) in Nepal to be short-term and reactive. We use an interacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 49 publications
(34 reference statements)
0
15
0
Order By: Relevance
“…Institutional change and flexibility to enable adaptation are a key challenge as the adaptive management approaches are new to the existing bureaucratic systems in these counties (Ford et al 2015;Nightingale 2017;Vij et al 2017Vij et al , 2018. However, there are limited studies to assess the overall effectiveness of adaptation actions taken at local, sub-national, and national levels (Ford et al 2015;Rahman et al 2018).…”
Section: Climate Policies At Different Levels and Institutional Setupmentioning
confidence: 99%
“…Institutional change and flexibility to enable adaptation are a key challenge as the adaptive management approaches are new to the existing bureaucratic systems in these counties (Ford et al 2015;Nightingale 2017;Vij et al 2017Vij et al , 2018. However, there are limited studies to assess the overall effectiveness of adaptation actions taken at local, sub-national, and national levels (Ford et al 2015;Rahman et al 2018).…”
Section: Climate Policies At Different Levels and Institutional Setupmentioning
confidence: 99%
“…This innovative model for supporting local adaptation action has been emulated in other mountainous countries such as India, Pakistan, Kenya, and Tanzania (Maharjan 2019). Nepal's LAPA programme provides a formal framework for identifying local adaptation needs, integrating sub-national priorities into national-level adaptation planning, and, in turn, accessing support to implement local-level adaptations (Silwal et al 2019); it receives major implementation support from the Nepal Climate Change Support Programme (NCCSP) (Vij et al 2019). These efforts were complemented by subsequent policies aimed at facilitating the integration of climate concerns into broader development plans and programmes (see NPC Fig.…”
Section: The Architecture Of Unfccc Adaptation Initiativesmentioning
confidence: 99%
“…Nightingale (2017) has demonstrated that struggles for authority and recognition have strongly influenced adaptation policies and institutions in Nepal, with attendant effects on where, how, and for whom adaptation assistance becomes available across rural Nepal. Similarly, Vij et al (2019) highlight how power asymmetries among participants in LAPA planning meetings led to the prioritization of actions that reflected the preferences of specific actors, primarily the facilitators of meetings and local politicians, not community members. As such, adaptation planning activities can actually reinforce, rather than alleviate, the social conditions that shape differentiated vulnerabilities (Nagoda and Nightingale 2017).…”
Section: Progress In Meeting Adaptation Needsmentioning
confidence: 99%
“…knowledge frameworks); they also determine how different groups are positioned in relation to this framing (e.g. as agents of change or powerless victims) and are thus able to steer adaptation choices 1174 Progress in Human Geography 45( 5) (Eriksen et al, 2015; see also Barnett, 2020;Vij et al, 2019). Although urban climate governance involves many state and non-state actors, including NGOs, the private sector, international funding bodies and communities (Castán Broto, 2017), local (municipal) governments remain the central actors that shape (short-term) adaptation planning (Bulkeley and Betsill, 2013), particularly in the Global South.…”
Section: Adaptation Politics: Uneven Power Relations and The Articulation Of Political Authoritymentioning
confidence: 99%